Compact Stellar X-Ray Sources 2006
DOI: 10.1017/cbo9780511536281.005
|View full text |Cite
|
Sign up to set email alerts
|

Black hole binaries

Abstract: keV for a Crab-like spectrum with photon index Γ = 2.1. Table 4.1. Confirmed black hole binaries: primary properties Source Alternative Year b Type c Fx,max D P orb Spec. References name a (µJy d ) (kpc) (hr) 0422+32 V518 Per 1992/1 L,T 3000 2.6 ± 0.7

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

48
703
4
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 840 publications
(758 citation statements)
references
References 211 publications
(336 reference statements)
48
703
4
3
Order By: Relevance
“…In addition to the above standard filters, we only used X-ray events within the energy range of 3-13 keV which translates to PCA channels 7-32. This energy range is comparable -17 -to the bandpass in which high-frequency quasi-periodic oscillations have been reported from stellar-mass black holes 10,14,15 . Moreover, beyond 13 keV the background dominates the overall count rate by a factor greater than 10.…”
Section: Methodssupporting
confidence: 57%
See 2 more Smart Citations
“…In addition to the above standard filters, we only used X-ray events within the energy range of 3-13 keV which translates to PCA channels 7-32. This energy range is comparable -17 -to the bandpass in which high-frequency quasi-periodic oscillations have been reported from stellar-mass black holes 10,14,15 . Moreover, beyond 13 keV the background dominates the overall count rate by a factor greater than 10.…”
Section: Methodssupporting
confidence: 57%
“…M82 X-1's previous mass estimates of a few hundred solar masses combined with the Type-C identification 2,4,9 of its mHz X-ray quasi-periodic oscillations suggest that 3:2 ratio, twin-peak, high-frequency oscillations analogous to those seen in stellar-mass black holes, if present, should be detectable in the frequency range of a few Hz 16 . We accordingly searched Rossi X-ray Timing Explorer's (RXTE's) proportional counter array archival data to look for 3:2 oscillation pairs in the frequency range of [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Hz which corresponds to a black hole mass range of 50-2000 M ⊙ .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…McClintock & Remillard (2003) found that the upper QPO frequency in microquasars scales well as ν U = 2.793(M 0 /M ) −1 kHz which is in good agreement with the 1/M scaling of the first term in equation (1.1).…”
Section: Troubles With the Spin: 1/m Scalingsupporting
confidence: 76%
“…Resonance between such a frequency modes which proposed by Kluzniak and Abromowicz [23] can be a physical mechanism for existing Quasi-periodic oscillations (QPOs). QPOs in the X-ray fluxes of some astrophysical objects such as a neutron star and black hole sources have been reviewed by many researches including van der Klis [42] and McClintock et al [30]. Johannsen [18] has examined the radial and vertical epicyclic frequencies in the Kerr-like metric.…”
Section: Introductionmentioning
confidence: 99%